LONG-TERM MACROECONOMETRIC MODEL FOR THE POLISH ECONOMY - Welfe, Władysław (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
Development of market economies towards economies based onknowledge implies the construction of new long-term macroeconometricmodels. The structure and use of the long-term W8D model for Poland wasshown. This is a complete model that explains production and the factors itsgrowth including R&D and human capital and also final demand allowing forstudies of potential disequilibria. It is closed by equations explaining prices,wages and financial flows. The simulation version is includes 235 equations,of which 111 are stochastic. It is used in long-term growth scenarios up to theyear 2030.